2016
DOI: 10.1016/j.eurpsy.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum brain-derived neurotrophic factor levels following electroconvulsive therapy or antipsychotic treatment in patients with schizophrenia

Abstract: BDNF level was lower in schizophrenia patients relative to healthy controls before ECT and medication. BDNF level increased after ECT and medication, and its longitudinal change was associated with changes in patients' psychotic symptoms. These results indicate that BDNF mediates the antipsychotic effects of ECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 49 publications
1
38
5
1
Order By: Relevance
“…Many theories of the mechanisms of action of ECT have been proposed, including the enhancement of dopamine synthesis and turnover, 42 direct effects of convulsions, 43 and increases in the secretion of BDNF 8, 9 and neurogenesis. 44 These hypotheses have gained traction from experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theories of the mechanisms of action of ECT have been proposed, including the enhancement of dopamine synthesis and turnover, 42 direct effects of convulsions, 43 and increases in the secretion of BDNF 8, 9 and neurogenesis. 44 These hypotheses have gained traction from experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that ECT in schizophrenia patients alters cerebral blood flow in the prefrontal cortex (PFC), 6 increases structural network strength in the medial temporal lobe (MTL) network and lateral prefrontal/cingulate cortical network, 7 increases brain-derived neurotrophic factor (BDNF) levels, 8, 9 and improves psychotic symptoms. These results suggest that ECT can alter brain connectivity patterns, thereby alleviating symptoms of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the positive effects of ECT every other day have been reported for the PANSS and BPRS indices for TRS [17-20]. Furthermore, other studies have confirmed the positive effects of a combination of ECT and drugs such as clozapine and antipsychotics on schizophrenic patients’ psychiatric symptoms as measured with the BPRS and PANSS [14, 39-41]. …”
Section: Discussionmentioning
confidence: 63%
“…In a meta-analysis, Gu et al [40] described findings consistent with the present study and concluded that, for patients with schizophrenia, treatment with ECT (without concurrent use of antipsychotics), or the combination of ECT and antipsychotics, was associated with a decrease in the PANSS score. Li et al [41] found that the PANSS score in patients with schizophrenia decreased from baseline to discharge during the use of ECT. Jiang et al [17] observed that PANSS scores dropped after 7 or 8 sessions of the use of ECT (given every second day) in women with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we measured serum brain derived neurotrophic factor (BDNF) in 160 schizophrenia patients between the ages of 16 and 65 before and after treatment with antipsychotic agents and ECT, and we found that both treatments increased serum BDNF (27). Many studies have examined BDNF levels in schizophrenia and revealed that BDNF influences the therapeutic mechanisms of ECT (28)(29)(30).…”
Section: Thus We Speculated That Abnormal Expression Of Egf May C O mentioning
confidence: 97%